The National Basketball Association's (NBA) Digital Transformation: An Explanatory Case Study - James Santomier; Harald Dolles; Reinhard Kunz (Nicolaus Copernicus University in Toruń, 2023)
Purpose. Digital transformation in the global sport industry has resulted in digitally focused business strategies, innovative business models, targeted social media marketing strategies, increased consumer, and sponsor demand, accelerated growth in women's sports, and streaming media (OTT) worldwide. This paper aims to study the case of the U.S.-based National Basketball Association's (NBA) digital transformation, including multiple interactions of actors in the digital transformation process. A key aim is understanding the synergies resulting from the league's integration of digital technologies, its business strategy, the evolution of its hybrid business model and the increase in revenue and global branding.   Design/methodology/approach. An explanatory case study design was selected to examine the NBA's integration of digital technologies, digital and social media marketing strategies, business model innovation, multimedia partnerships, and strategic sponsorships. Data was derived from: (1) academic journals; (2) research based white papers; (3) sport industry reports and periodicals; (4) selected sport industry websites; and (5) recorded interviews with selected NBA officials. Gleaned content was analysed with a theory-oriented triangulation approach. The study period was from 2000 to 2023.    Findings. The NBA's digital transformation, led by an entrepreneurial management team contributed to a successful business strategy aimed at engaging with digitally focused consumers across multiple media channels. The NBA developed an ecosystem-based consumer-focused hybrid business model, content-focused digital assets, and partnerships with media, brands, and cultural events. Its media partnerships and strategic sponsorships are synergistic with its business and marketing objectives, digital initiatives, and acquisitions. By the 2017-2018 season, the NBA had validated its position as a successful global entertainment property.   Originality/value. This paper examined the NBA's digital transformation, including how the league integrated digital technologies with its business strategy and model to increase revenue and create a global brand. The analysis examined how the NBA's digital transformation facilitated the league's business strategy, enhanced the NBA fan experience, generated revenue from innovative digital products and services, and transformed its business model. The NBA's business strategy and hybrid business model provide an exemplar for professional teams, leagues, and federations worldwide seeking to digitally transform their enterprises.